Experimental transmission and electron microscopic demonstration of the virus of haemorrhagic disease of rabbits in Czechoslovakia - Smíd, B; Valícek, L; Stĕpánek, J; Jurák, E; Rodák, L (Zentralblatt für Veterinärmedizin. Reihe B., 1989)
Intramuscular administration of the filtrate of organ suspensions, prepared from a dead rabbit, killed 62.9% of inoculated rabbits within 1 to 5 days, while 93.3% died after intranasal administration of the same inoculum. The virus survived freeze-drying and was resistant to treatment with 0.4% formaldehyde when incubated at 37 degrees C for 1 hour and 4 degrees C for the subsequent 12 hours, but lost its infectivity when the treatment was prolonged to 3 hours at 37 degrees C and 3 days at room temperature. Its infectivity was also inhibited by reconvalescent serum. The virus could not be detected after 3 passages in primary rabbit kidney cell cultures. Electron microscopy of negatively stained preparations demonstrated icosahedral virus particles with a diameter of 29 to 33 nm without an envelope. Accurate morphological classification has not yet been completed. Incubation with a reconvalescent serum, diluted 1:20 or 1:40, resulted in the formation of immune complexes, detectable by electron microscopy.
Keywords: hemoragické horečky virové; Hemorrhagic Fevers, Viral; elektronová mikroskopie; Československo; pikornavirové infekce; Picornaviridae Infections; Czechoslovakia; Animals; Microscopy, Electron; Rabbits; Caliciviridae; králíci; zvířata